Review: Technological and organoleptic issues pertaining to cheeses with denomination of origin manufactured in the Iberian Peninsula from ovine and caprine milks - Freitas, A.C (2011)
A few European countries have created Appélations d'Origine Protegée (AOP) in order to support legal protection and hence promote enforcement of high-quality standards of selected food products. This paper comprehensively reviews and updates fundamental and applied aspects encompassing tech nological and organoleptic characteristics of AOP traditional cheeses manufactured in the Iberian Peninsula, from ovine and/or caprine milks. Those cheeses from Portugal and Spain can be divided into four distinctive groups, based on milk source and rennet type: (i) Azeitão, Castelo Branco, Évora, Nisa, Serpa, Serra da Estrela and La Serena cheeses, manufactured with raw ovine milk and coagulated via plant rennet; (ii) Terrincho, Idiazábal, Manchego, Roncal and Zamorano cheeses, elaborated with raw ovine milk and coagulated via animal rennet; (iii) Cabra Transmontano and Majorero cheeses, manufac tured with raw caprine milk and coagulated via animal rennet; and (iv) Amarelo da Beira Baixa, Picante da Beira Baixa and Rabaçal cheeses, manufactured with mixtures of raw ovine and caprine milks and coagulated via animal rennet. Considerable differences between Portuguese and Spanish AOP cheeses exist; the former are, in general, characterized by softer consistencies and similarities to one another in terms of manufacturing protocols (usually encompassing coagulation of plain raw milk followed by slow draining of the curd), whereas the latter are, in general, larger and firmer.